PENGARUH SOCIAL MEDIA MARKETING TERHADAP KEPUTUSAN PEMBELIAN JASA GPHOTO - Andri Budi Santosa; Yulies Rianto (Economicus : Jurnal Ekonomi dan Manajemen, 2021)
Founded in 2009, at that time Gphoto was still called Arppegiano Photography, started as a hobby that needed financial support to keep going, finally choosing the wedding photography genre that was considered the most profitable in the short term. From 2009 to 2015, Arppegiano Photography still only relied on word of mouth sales, from acquaintances and partners of bridal makeup vendors, at that time sales were still small, and insignificant. The type of research used in this research is causal research. In this study, the purpose of the causal study is to provide an explanation of the influence of digital marketing on the decision to purchase Gphoto services. The partial test (t-test) shows that the Instagram digital marketing variable has a significant influence on the decision to purchase Gphoto services, because the t-count value is greater than t-table. The partial test (t-test) shows that Facebook's digital marketing variable does not have a significant influence on the decision to purchase Gphoto services. Because the value of t count is smaller than t table. The partial test (t-test) shows that the Whatsapp digital marketing variable has a significant influence on the decision to purchase Gphoto services, because the t-count value is greater than t-table. Simultaneously, Instagram digital marketing, Facebook digital marketing, Whatsapp digital marketing have a significant effect on service purchase decisions.